Ethnicity, N. 4 : Ethnic Identities and Integration of the Society - (:unkn) unknown (Daugavpils Universitātes Sociālo pētījumu institūts, Latvijas Universitātes Filozofijas un socioloģijas institūts, 2011)
The articles published in this issue analyse the problem of the integration of social and ethnic identities.
"Ethnicity" – a peer-reviewed journal was established by the Institute of Social Investigations (Daugavpils University, Latvia) and the Institute of Philosophy and Sociology (University of Latvia). The journal publishes original works about ethnicity in different fields of knowledge – sociology, history, social linguistics, social psychology, law, political science.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Ethnology; identity; ethnic identity; integration; ethnic diversity; multiculturalism; global diversity